Upaya Promotif Pencegahan Demam Berdarah Dengue di Lingkungan Panti Asuhan - Maksuk, Maksuk; Debi Mardiana; Farach Labita Anissa Putri; M. Deffa Anugrah; Ahmad Rifqi Al-Hanif; Ranti Rahmadini (Poltekes Kemenkes Tanjungpinang, 2024)
Dengue fever is a disease transmitted through the bite of the Aedes aegypti mosquito and is endemic in Palembang City with a trend of increasing cases from 2020 - 2022, with the highest number of cases in 2022, namely 908 cases. This disease can attack all ages, with dense housing density, one of which is in orphanages. This activity aims to increase the knowledge of children and administrators in orphanages about preventing dengue fever transmission. The method of implementing this activity is counseling with leaflets and educational videos on preventing dengue fever. This activity is carried out in three stages, namely preparation, implementation and evaluation. The target audience is the administrators and children of orphanages in Palembang City. The evaluation uses process evaluation, which is carried out during the activity process. The results of measuring the level of knowledge in efforts to prevent dengue fever are that there is a difference in the level of knowledge before and after counseling from the activity, namely increasing knowledge among administrators and children in orphanages in preventing dengue fever. The outcome criteria are that children can answer all questions asked during the counseling activity and children take the counseling seriously and enthusiastically. Dengue fever prevention activities through counseling Dengue fever prevention needs to be carried out continuously and continued by working together with the health center.